2020
DOI: 10.1590/1678-4162-11848
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of gastrointestinal parasitic diseases of swine in different production phases in commercial pig farms from the State of Santa Catarina, southern Brazil

Abstract: Gastrointestinal parasites are important, since they can cause a decrese in the performance of swine. The occurrence of parasites in pig farms can create economic losses such as reduction in the value of carcasses and increasing expenses with medicines and veterinary assistance. This study aimed at investigating the occurrence of intestinal parasites in different phases of production reared pigs in intensive prodution systems in the western region of the State of Santa Catarina. A total of 403 fecal samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…( 2017 ) (49.4%; 131/265), Pradella et al. ( 2020 ) (51.86%; 209/403) and Yadav et al. ( 2021 ) (56.65%; 438/769).…”
Section: Discussionmentioning
confidence: 96%
“…( 2017 ) (49.4%; 131/265), Pradella et al. ( 2020 ) (51.86%; 209/403) and Yadav et al. ( 2021 ) (56.65%; 438/769).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, I. suis was detected at a prevalence of 16.05%, which was higher than the 6% reported in prior studies in Greece [ 19 ], but lower than that reported in Sweden (60%) [ 5 ], Central Africa (65.38%) [ 23 ] and Nan province, Thailand (25.7%) [ 26 ]. I. suis is a predominant clinical protozoan parasite in pigs that can lead to transient diarrhea, often caused by secondary pathogens such as bacteria and viruses, resulting in weight loss and increased management costs [ 3 ]. I. suis infections are a major cause of diarrhea in suckling pigs, typically detected at around 8–10 days of age, but older piglets may also be affected [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The timing of drug administration should be consistent with the protozoan life cycle. The 3 rd day of piglet life is the optimal time for antiprotozoal medication [ 3 ]. Farrowing units are a major source of infection in newborn piglets, which highlights the need for hygienic measures in farrowing pens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations